Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s11412-009-9063-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploring metaskills of knowledge-creating inquiry in higher education

Abstract: The skills of knowledge-creating inquiry are explored as a challenge for higher education. The knowledge-creation approach to learning provides a theoretical tool for addressing them: In addition to the individual and social aspects in regulation of inquiry, the knowledge-creation approach focuses on aspects related to advancing shared objects of inquiry. The development of corresponding metaskills is suggested as an important longterm goal for higher education; these pertain, simultaneously to the individual,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…The current findings suggest that materializing knowledge, whether in a preliminary or advanced form of elaboration, into situational objects (Jahreie 2010) serves to preserve the continuity of the process. It also aids the progressive accumulation of conceptualizations and elaborations (Muukkonen and Lakkala, 2009) and contributes to the co-construction process by freezing the generated knowledge at particular moments during the process. As stated earlier, the knowledge object drafts played a catalyzing role in the groups' interactions, and that was also expressed in how the course of the interaction changed or adjusted with time, in order ultimately to become meaningful for the co-construction of the objects.…”
Section: Multi-layeredness and Temporalitymentioning
confidence: 99%
“…The current findings suggest that materializing knowledge, whether in a preliminary or advanced form of elaboration, into situational objects (Jahreie 2010) serves to preserve the continuity of the process. It also aids the progressive accumulation of conceptualizations and elaborations (Muukkonen and Lakkala, 2009) and contributes to the co-construction process by freezing the generated knowledge at particular moments during the process. As stated earlier, the knowledge object drafts played a catalyzing role in the groups' interactions, and that was also expressed in how the course of the interaction changed or adjusted with time, in order ultimately to become meaningful for the co-construction of the objects.…”
Section: Multi-layeredness and Temporalitymentioning
confidence: 99%
“…Collaborative learning and peer teaching has been used in many ways in various disciplines to support students' learning of challenging topics (Nnodim, 1997;Brueckner and MacPherson, 2004;Youdas et al, 2008), including anatomy (Thurman et al, 2009;Khosa et al, 2010;Salomäki et al, 2014). However, the success of group work and peer teaching depends significantly on students' ability to effectively communicate and collaborate (Allen and Boraks, 1978;Evans and Cuffe, 2009;Muukkonen and Lakkala, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Damşa et al (2010) reported on students' learning about the regulative and epistemic aspects of collaboration, particularly the benefits of shared epistemic agency in relation to the advancement of shared outcomes. Other studies (Muukkonen & Lakkala, 2009;Muukkonen, Lakkala, & Hakkarainen, 2005) have used open-ended questions to solicit students' self-evaluation of competence learning during courses. These have provided evidence of learning about domain-specific competences, e.g., designing software architecture or setting up a business plan, as well as domain-generic competences such as learning to coordinate teamwork, taking initiative, creating new knowledge, integrating theory and practice, and collaborating with work-life experts.…”
Section: In Digital Environmentmentioning
confidence: 99%
“…Prior research and available assessment instruments have primarily focused on explicating individual dimensions of generic competences, including, e.g., critical and analytical thinking (e.g., Hyytinen et al, 2015;Kember & Leung, 2009), problem-solving (Neubert, Mainert, Kretzschmar, & Greiff, 2015), self-management of learning, communication skills, and information and digital literacy (e.g., Strijbos et al, 2015;Young & Chapman, 2010). Other research has shown that there are collective dimensions to be taken into account in competence development: collaborative idea generation and knowledge production, as well as epistemic, regulative, and metacognitive competence utilized in shared knowledge advancement (Damşa, 2014;Damşa, Kirschner, Andriessen, Erkens, & Sins, 2010;Hadwin, Järvelä, & Miller, 2011;Muukkonen & Lakkala, 2009;Panadero, Kirschner, Järvelä, Malmberg, & Järvenoja, 2015). These involve dimensions of competence required in collaborative working often referred to as interpersonal, reciprocal communication, and teamwork capabilities.…”
Section: Introductionmentioning
confidence: 99%